2022
DOI: 10.3846/jcem.2022.16580
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Approach for Tendering Practice at the Pre-Contract Stage: The Uk Practitioner’s Perspective

Abstract: Tender documents often lack clarity and are incomplete, making it difficult for contractors to appropriately price projects. A general view is that the quality of tender documents has declined, which has affected the bidding strategies of contractors. However, the academic literature has focused mainly upon the views of contractors. To obtain a more balanced view of tendering practices, in-depth interviews were conducted with 10 practitioners (client, consultant, and contractor) who are involved in a common pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…By contrast, both the client and the consultant agreed that the quality of tender documents is an ongoing issue (Khoso 2021). During the study it was revealed that tendering practice is influenced by the relationship between stakeholders or the unbalanced access to information rather than the accuracy and analysis of tender documentations (Whang 2022, Cole 2013.…”
Section: Literature Reviewmentioning
confidence: 97%
“…By contrast, both the client and the consultant agreed that the quality of tender documents is an ongoing issue (Khoso 2021). During the study it was revealed that tendering practice is influenced by the relationship between stakeholders or the unbalanced access to information rather than the accuracy and analysis of tender documentations (Whang 2022, Cole 2013.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In-depth interviews are frequently used to collect data in qualitative research (Whang et al, 2022). Conversations between interviewers and interviewees lead to an exchange of opinions and ideas (Shoar & Banaitis, 2019).…”
Section: In-depth Interviewsmentioning
confidence: 99%